Pruritus after continuous administration of epidural morphine for post-cesarean delivery analgesia: a case control study - Xinyi Tian; Kaifan Niu; Hong Cao; Gonghao Zhan; Yan Zhang; Feng Xu; Wangning Shangguan; Ye Gao (BMC, 2021)
Abstract Background Pruritus is one of the most common side effects of epidural morphine administered for post-surgery analgesia, and pregnant women tend to be highly susceptible. The relative contributions of morphine concentration, local anesthetics, and level of pain to pruritus after epidural morphine for post-cesarean delivery analgesia remain unclear. Accordingly, the present study aimed to identify risk factors for pruritus after continuous administration of epidural morphine for post-cesarean delivery analgesia. Methods This case control study was based on routinely collected clinical data. Participants included women who had undergone cesarean section and adopted a patient-controlled analgesia pump for postoperative analgesia. A series of logistic regression analyses were performed. Interaction terms were added to explore the moderation effects of combined local anesthetics and pain level on associations between morphine concentration and pruritus. Robustness of the results was checked through sensitivity analysis using propensity scores matching approach. Results Higher morphine concentration, assisted reproductive treatment, and multipara and cesarean section history were significantly more prevalent in the pruritus group than in the control group. The probabilities of pruritus at morphine concentrations of 10, 15, 20, 25, 30 and 40 μg/mL increased sequentially from 0.05, 0.1, 0.2, 0.35, 0.54 to 0.84, respectively. The trend remained steep in the ropivacaine stratum and became flatter when combined with levobupivacaine. At mild pain combined with levobupivacaine, the incidence of pruritus increased from 0.33 (95% confidence interval [CI] 0.1-0.68) in the 10 μg/mL morphine group to 0.48 (95% CI 0.1-0.88) in the 40 μg/mL morphine group. In the stratum of moderate pain combined with levobupivacaine, the incidence increased from 0.4 (95% CI 0.04-0.92) to 0.56 (95% CI 0.03-0.98). The results in the sensitivity analysis were in consistent with above findings. Conclusions Higher concentrations of morphine, multipara, and assisted reproductive treatment were factors associated with a higher probability of pruritus. Pain level or combined local anesthetics could moderate the association between morphine concentration and pruritus.